Social Vulnerability Index Is Associated With Major Morbidity After Lung Resection - Savan K. Shah, MD; Arsalan A. Khan, MD; Sanjib Basu, PhD; Gillian C. Alex, MD; Nicole M. Geissen, DO; Michael J. Liptay, MD; Christopher W. Seder, MD (Annals of Thoracic Surgery Short Reports)
Background: Little is known about the prognostic impact of the Social Vulnerability Index (SVI) in patients with early-stage non-small cell lung cancer (NSCLC) who are undergoing video-assisted thoracoscopic lung resection. Methods: Patients who underwent lung resection for stage IA-IIB NSCLC at a single institution between 2010 and 2021 were included in the study. The Society of Thoracic Surgeons definition of major morbidity, consisting of 14 postoperative events, was used. The SVI was determined by geocoding the permanent addresses of Illinois residents and using the Centers for Disease Control and Prevention calculator for a census-tract level SVI. Univariate and multivariate logistic regression analyses were used to examine the association between the SVI and major morbidity. Cut-point analysis was performed to determine the SVI cutoff that most strongly correlated with major morbidity. Results: A total of 551 patients met inclusion criteria, and 65% (356 of 551) of these patients underwent lobectomy. The SVI cutoff was determined to be 0.831 (P = .010). In the high-SVI cohort , 58% (26 of 45) were Black, compared with 9% (45 of 506) in the low-SVI cohort (P < .001). For high-SVI patients, the major morbidity rate was 27% vs 9% for low-SVI patients (P = .0174), and the 1-year mortality rate was 8.9% vs. 3.0% for those with a low SVI (P = .061). On univariate analysis, high SVI status was associated with 30-day major morbidity (odds ratio, 2.84; CI, 1.28-6.29; P = .010). On multivariate analysis, after controlling for age, race, sex, tumor histologic type, procedure type, preoperative comorbidities, smoking history, and forced expiratory volume in 1 second, this association persisted (odds ratio, 3.16; CI, 1.11-8.99; P = .031). Conclusions: A high SVI is associated with major morbidity after video-assisted thoracoscopic lung resection for NSCLC.